The things they carried : a work of fiction - O'Brien, Tim, 1946- (Boston : Houghton Mifflin Harcourt, 2009)
Heroic young men carry the emotional weight of their lives to war in Vietnam in a patchwork account of a modern journey into the heart of darkness.
Keywords: Vietnam War, 1961-1975 -- Veterans -- Fiction; War stories, American